Identifying Subsets of Cancer Patients with an Increased Risk of Developing Cutaneous Melanoma: A Surveillance, Epidemiology, and End Results–Based Analysis - Thomas Z. Rohan; Jenna L. Mandel; Henry Y. Yang; Lauren Banner; Daniel Joffe; Rachel Zachian; Jaanvi Mehta; Safiyyah Bhatti; Tingting Zhan; Neda Nikbakht (JID Innovations)
Cancer survivors have an increased risk of developing second primary malignancies. We aimed to identify whether certain cancers lead to an increased risk of developing melanoma among cancer survivors. We evaluated the risk of developing cutaneous melanoma after the 20 most common cancers in the United States through the Surveillance, Epidemiology, and End Results database. We identified 9 primary cancers linked to increased risk of developing a subsequent cutaneous melanoma: cutaneous melanoma (standardized incidence ratio [SIR] = 9.65), leukemia (SIR = 1.76), non-Hodgkin lymphoma (SIR = 1.33), thyroid cancer (SIR = 1.32), brain and nervous system cancer (SIR = 1.31), myeloma (SIR = 1.23), breast cancer (SIR = 1.13), oral cavity/pharynx cancer (SIR= 1.12), and prostate cancer (SIR = 1.03). The risk of developing melanoma was highest 1–5 years after diagnosis of most primary cancers. Notably, individuals aged under 50 years with a prior melanoma had a 14-fold increased risk. Our findings highlight specific at-risk groups—such as those aged under 50 years with recent melanoma, individuals in their 60s diagnosed with leukemia, and those aged over 80 years with recent thyroid cancer—who may benefit from heightened clinical vigilance and tailored melanoma screening strategies.